Welfare of aquatic animals: where things are, where they are going, and what it means for research, aquaculture, recreational angling, and commercial fishing. (15th June 2018) - Browman, Howard I; Cooke, Steven J; Cowx, Ian G; Derbyshire, Stuart W G; Kasumyan, Alexander; Key, Brian; Rose, James D; Schwab, Alexander; Skiftesvik, Anne Berit; Stevens, E Don; Watson, Craig A; Arlinghaus, Robert
Abstract: We revisit the evidence attributing sentience-pain-suffering to aquatic animals. The objective is to inform readers of the current state of affairs, to direct attention to where research is needed, and to identify "wicked" questions that are difficult to resolve unequivocally. By separating the ethical from the scientific debate, applying organized skepticism to the latter, and taking a pragmatic approach that does not depend on resolving the "wicked" questions, we hope to focus and strengthen research on aquatic animal welfare. A second but closely-related objective is to briefly summarize the research used to support the regulations governing the welfare of aquatic animals, particularly its limitations. If you interact with aquatic animals, these regulations already affect you. If the regulatory environment continues on its current trajectory (adding more aquatic animal taxa to those already regulated), activity in some sectors could be severely restricted, even banned. There are surely some lively debates and tough choices ahead. In the end, extending legal protection to aquatic animals is a societal choice, but that choice should not be ascribed to strong support from a body of research that does not yet exist, and may never exist, and the consequences of making that decision must be carefully weighed.